Mediating effects of meaning in life on the relationship between family care, depression, and quality of life in Chinese older adults - Zhou, Jing-Jing; Zhang, Yu; Ren, Qing-Zhuo; Li, Ting; Lin, Gui-Ding; Liao, Min-Yi; Chen, Shao-Hua; Tong, Pei; Gao, Yu-Lin (Frontiers in Public Health, 2023)
Backgroud: Explore sources of meaning of older adults and action path between family care, meaning, quality of life, and depression. Materials and methods: 627 older adults were investigated by using the Sources of Meaning in life Scale for the elderly (SMSE), Family Care Index (APGAR), the Center for Epidemiological Studies Depression Scale-10 (CES-D-10), and the EuroqOL-5 Dimensions (EQ-5D). Results: 454 older adults with good family function, 146 with moderate (99) and severe (47) family dysfunction, 110 with depression. The structural equation model showed that family care affected quality of life and depression by influencing meaning, and depression had a significant negative effect on quality of life (P＜0.05). The model fitted well (c2/df=3.300, SRMR=0.0291, GFI=0.975, IFI=0.971, TLI=0.952, CFI=0.971, RMSEA=0.062). Conclusion: Meaning in life as an intermediary factor affect depression and quality of life. The SMSE can be used to quickly clarify the sources of meaning, improve meaning, promote mental health.